The content of proximate, beta carotene, and organoleptic pumpkin mooncake as a snack to improve the immune system in the elderly - Margaretha Heny Widayati; Nani Ratnaningsih; Badraningsih Lastariwati (AcTion: Aceh Nutrition Journal, 2023)
The elderly population continues to increase, so it is necessary to provide healthy foods that can boost their immune system, one of which is pumpkin. Pumpkin contains β-carotene, an antioxidant and anti-inflammatory to boost the immune system. This study aimed to develop pumpkin mooncakes for the elderly and analyze their proximate, beta-carotene, and organoleptic values. Research design uses the research and development (R&D) method with a 4D design, namely, defining, designing, developing, and disseminating. The study was conducted in Surakarta City in December 2021. Eighty older adults participated in the organoleptic test. Mooncake products were subjected to organoleptic examination and proximate analysis using the ANOVA test with a significance level of 95%. The results of the proximate analysis consisted of water content (38,91%), ash (0,74%), fat (5,80%), protein (2,20%), and carbohydrates (53,24%). The β-carotene content of the pumpkin mooncake increased by 28,42% compared to that of the reference product. The average liking was 4,69, and there was a difference in the level of panelists' liking for development and reference products (p= 0,020). In conclusion, pumpkin mooncake is a beneficial ingredient that supports the immune system. However, further research is needed to compare it with other healthy foods in the context of improving immunity in the elderly population.